GPS Tracking Kapal Laut Menggunakan Web Service Skywave dan Google Maps API V3 Pada PT. Mitra Sarana Utama Indonesia - Sinurat, Dermanto; Mahendra, Irfan (LPPM STMIK ANTAR BANGSA, 2017)
AbstractÃ¢â‚¬â€Utilization of GPS technology to determine the position of a moving object, are now commonly found, such as on land transportation, air and sea transport. One provider of GPS module is Skywave. Some weaknesses in GPS Skywave today, is like information about the ship's position. Skywaves GPS can not provide information about the position of all ships at once, but could only provide information to ship one by one. Other than that, information about the ship cruise lines are also seen as less informative, because GPS Skywaves gives no special mark on the start position and end position taken by cruise ship. Skywave website also does not provide a history of the cruise ships that can be accessed by the customer in accordance with the desired date. So that needs to be built GPS Tracking Apps web-based ships that can be used to monitor the position of the ship, whose data is taken directly from the Server Skywave by using a web service that has been provided. GPS Tracking Ships can store all the history cruise ship into a database on a server PT. Mitra Sarana Utama Indonesia. Thus it can be re-displayed information according to the time selected by Customer. Customers can also display all customer ship position coordinates in the google map. Shipping route information is shown to be more informative to begin with the symbol